Diversification Benefits of Malaysian REITs in the COVID-19 Periods - Nurulhusna Adibah Mohamad Nasir; Muhammad Zaim Razak; Shahrina Ismail (Malaysian Journal of Science Health & Technology, 2025)
This study examined the diversification benefits of Malaysian real estate investment trusts (REITs) in a mixed-asset portfolio of stocks and bonds during the COVID-19 period. Monthly data were used from January 2018 to October 2023. The sample time frame consisted of overall periods, as well as the subperiods before, during, and after the COVID-19 period. The risk-adjusted return for each asset and the correlation between Malaysian REITs, stocks, and bonds were analyzed. For each time frame considered, a mean-variance portfolio analysis was performed for two separate scenarios that include a portfolio with and a portfolio without REITs. In each scenario, average portfolio performance was evaluated. Malaysian REITs generally reported a superior risk-adjusted return over other financial assets overall and in each of the subperiods of COVID-19. During the COVID-19 period, REITs had a positive correlation with stocks but negative correlation with bonds. The results of the mean-variance analysis indicated the diversification benefits of incorporating REITs irrespective of overall as well as the periods before, during, and after COVID-19. The portfolio with REITs had a higher risk-adjusted return and a lower level of risk when compared to a portfolio consisting of stocks and bonds. The findings of the study highlight the diversification benefits of Malaysian REITs, which suggest the resilience of liquid real estate assets, particularly during and after the COVID-19 period. The resilience was contributed by the fundamental aspects of tenants and the underlying properties of Malaysian REITs. Investors in the Malaysian market should include REITs in their portfolio despite short-term uncertainty in an attempt to recoup the gains upon the onset of the recovery from the COVID-19 pandemic.